Exercises that suport the physical functioning in elderly adults with sarcopenia - Medina-Fernández, Isaí Arturo (Universidad de Sonora, 2019)
Introduction: Sarcopenia is a health problem associated with the increase of elderly adults with little or no physical activity and whose effects are related to functionality, this disease is diagnosed when there is a decrease in mass, strength and less physical performance. Currently, physical exercise is one of the best therapeutic options against sarcopenia. Development: Two points are described, the first one is the role of exercise in sarcopenia, which describes the importance and benefits of exercise in patients with this disease; the second point is the type of exercises for sarcopenia prevention, in this section the exercises identified such as progressive strength training, vibratory, aerobic, flexibility and balance exercises are described. Conclusion: Exercise interventions on elderly patients with sarcopenia cause significant changes in muscle strength, improvement of physical function, muscle mass, knee extension, march, balance, as well as march speed.